2020
DOI: 10.1016/j.tmaid.2020.101882
|View full text |Cite
|
Sign up to set email alerts
|

In-flight transmission of COVID-19 on flights to Greece: An epidemiological analysis

Abstract: Background The emergence in China in late 2019 and subsequent progression of a pandemic of a respiratory disease named coronavirus disease 2019 (COVID-19) was highly facilitated by international travel. We present 5 cases of probable in-flight transmission in Greece. Methods We studied international passengers arriving to or departing from Greece from February 26 through March 9, 2020. Contact tracing extended up to 4 days before the onset of symptoms and focused on clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 8 publications
2
35
0
2
Order By: Relevance
“…35 While IATA suggests that risk of in-cabin COVID-19 transmission is low 13 , COVID-19 has spread globally because of the movement of infected individuals by air travel. [9][10][11][12] Moreover, the IATA COVID-19 survey concluded that 36% of respondents would at least wait six months before considering traveling by air, with an additional 14% indicating they would not travel before a year or more from the moment the pandemic shows a true global decline and 5%…”
Section: Insert Figure 3 Herementioning
confidence: 99%
See 1 more Smart Citation
“…35 While IATA suggests that risk of in-cabin COVID-19 transmission is low 13 , COVID-19 has spread globally because of the movement of infected individuals by air travel. [9][10][11][12] Moreover, the IATA COVID-19 survey concluded that 36% of respondents would at least wait six months before considering traveling by air, with an additional 14% indicating they would not travel before a year or more from the moment the pandemic shows a true global decline and 5%…”
Section: Insert Figure 3 Herementioning
confidence: 99%
“…7 SARS-CoV-2 spread worldwide and was declared a global pandemic 8 in less than 3 months, driven principally by the movement of infected individuals by air. [9][10][11][12] The emergence of COVID-19 and its associated travel bans have reduced international passenger traffic. As of 8 October 2020, 1.2 billion passengers have travelled worldwide 13 , compared to the over 4.5 billion in 2019.…”
Section: Introductionmentioning
confidence: 99%
“…2 shows that even with open border, both entities are experiencing decreasing cases very similar to close border policies between each other. We further simulate infections during the trip (including in-flight [ 41 ] but not limited to) by doubling the number of infected people upon arrival comparing to the numbers at departure. The simulation suggests that even with a high infection rate on the road, both entities can withstand the imported risk and maintain a decreasing trend for both the identified new cases and the number of hospitalized patients over time.…”
Section: Resultsmentioning
confidence: 99%
“… Parker and Mahomed (2020) The role of hypoxia and thrombosis is underestimated during COVID-19; regular oximetry scanning should be implemented. Pavli et al (2020) Based on 18 international flights bound to Greece, revealed five cases of probable in-flight transmission among 2,224 passengers. Schwartz et al (2020) Based on a lack of infection on a flight from Guangzhou to Toronto, it is concluded that in-flight transmissions are rare; especially in the presence of face masks and milder symptoms.…”
Section: Impact On Passenger-centric Flight Experiencementioning
confidence: 99%